Assessment of Education and Research in Biomedical Informatics - van Bemmel, J.H. (Yearbook of Medical Informatics, 2006)
The existence and survival of university institutes is increasingly dependent on assessments of research and education. In many countries also departments of biomedical informatics are assessed at regular intervals, often as part of the review of a Medical or Health Sciences Faculty, or a Research School. The article underlines the importance of periodic evaluation of research and education in biomedical informatics.Quality assessment, if done by an independent review committee of peers, is a suitable instrument to obtain insight into the quality and accountability of both education and research. Key instruments for the assessment of education and research are welldefined protocols that are used for self-assessment. These selfassessment reports form the inputs for the independent review committee.The outcomes of the assessments are directly related to the quality of research, which is visible in publications in peer-reviewed journals. Internal quality management tools contribute to a large extent to the improvement of the quality of education and research.External assessment – review by peers – is increasingly used as the final step of an integral quality system for research and education. This is particularly important if the results of biomedical informatics R&D are to be applied in clinical practice. A positive outcome of an assessment can only be expected from a long-term investment in the quality of research and researchers who publish their results in peer-reviewed journals.
Keywords: Research; education; biomedicine; assessment; peer review; quality management